Tòpics retòrics dels textos hagiogràfics bizantins i catalans. - NARRO, ÁNGEL (Scripta)
This article is aimed to compare the main rhetorical topoi of the prologues of both Byzantine and Catalan Hagiographical texts. The starting point is the consolidation of Hagiography as a literary genre in Late Antique Greek and Byzantine literature and its influence on the development of Hagiography in the West, first on Latin and then on Romance texts from the Middle Ages. In this way, we will observe the use of similar rhetorical resources to introduce and embellish the texts and analyze the explanation of this issue and the different approaches to explore.